Comparison of different POS tagging techniques for some South Asian languages - Hasan, Fahim Muhammad (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.